Measurement of the average innovativeness change over time in the EU member states - Roszko-Wójtowicz, Elżbieta; Białek, Jacek (Journal of Business Economics and Management, 2019)
In the age of globalisation, implementation and commercialisation of new technologies are perceived as key elements determining competitiveness of particular countries, therefore, the growth of innovativeness is seen as the predominant direction of European Union society’s transformation into information society. The aim of the paper is to propose a procedure of measurement of innovativeness growth over time, with the Summary Innovation Index (SII) methodology as a starting point. The considered issue can be expressed by the following main question: how to measure the innovation performance dynamics for a selected group of countries (such as the EU-28, EU-15 or EU-13 countries) and for time intervals (not only for two moments of observations). This is an important inquiry since well-known innovativeness indices (SII, GII, or IOI) concentrate mainly on the provision of information about countries’ innovation performance for a specific year of observations. Due to this fact, changes occurring over longer time periods are rather neglected. The main result of the paper is a proposition of average innovativeness growth index. The index uses weights describing the employment share of a selected group of specialists (e.g.: scientists and engineers, research and development personnel) in relation to the economically active population.